Laser Application to Determine Aluminum Properties - Narjis Zamil Abdulzahra; Saad Naji Abood (Current Approaches in Science and Technology Research Vol. 4, 2021)
The structural, physical, and mechanical properties of aluminium after laser-induced shock peening (LSP) were investigated before and after depositing films of various metals (Cu, In, and Al). The deposition of single and double films was conducted, and the physical property (density), shockwave properties (shock pressure, particle velocity, and shock velocity), mechanical properties (stress, strain, Young’s s modulus, and Hardness) were calculated, Young’s s modulus measured of aluminum was measured by classical method (Tensile test) and by LSP technique, and it was found that the measured using LSP is closer to the standard value than classical method. Single film Cu and sandwich Al / Cu deposited on Al substrate showed an enhancement in the mechanical properties rather than other films, while the deposited films of (In, In / Cu, and Al /In) on Al substrate revealed more strain and higher ductility than others. The laser-induced shock wave has a great importance in viruses, industrial and medical applications.